Komorbid Diabetes Melitus Bukan Merupakan Faktor Risiko Long COVID-19 - Muhamad Rizky Pratama Kurniawan Rizky; Lelly Yuniarti Lelly; Umar Islami Umar (Bandung Conference Series: Medical Science, 2023)
Abstract. As many as 30% of COVID-19 patients have comorbid diabetes mellitus. Diabetes is suspected to cause worsening of symptoms and a prolonged duration of symptoms known as long COVID-19. The high number of COVID-19 cases in Indonesia will probably be directly proportional to the long incidence of COVID-19, in Indonesia there are as many as 63.5% of COVID-19 patients experiencing symptoms of long COVID-19. The purpose of this study was to analyze the relationship between comorbid diabetes mellitus and symptoms of long COVID-19. The method used in this research is case control analysis. The research subjects were 91 COVID-19 patients who had been hospitalized at SMC Tasikmalaya Hospital and Cideres Majalengka Hospital and had been declared cured, selected by purposive sampling technique. Processing data using fisher's exact test. The results showed that 50 subjects were male and 41 subjects were female. 51 subjects had a history of comorbid diabetes mellitus. There were 46 subjects experiencing symptoms of long COVID-19 with the most age range experiencing symptoms of long COVID-19 at the age of 41-60 years as many as 53 subjects and the least at age >60 years as many as 18 subjects. There was no significant relationship between co-morbid diabetes mellitus and symptoms of long COVID-19 with a p-value of 0.240 (>0.05). It was concluded that comorbid diabetes mellitus in COVID-19 patients is not a risk factor for the appearance of long-term symptoms of COVID-19. Keywords: COVID-19, diabetes mellitus, long COVID-19